Pengaruh Atmosfir Store, Brand Identity, Dan Social Media Marketing Terhadap Keputusan Pembelian Dengan Variabel Mediasi Minat Beli (Studi Empiris Pada Kedai Kopi Janji Jiwa) - Andriawan Pamungkas; Diesyana Ajeng Pramesti (Universitas Muhammadiyah Magelang, 2021)
This study aims to examine the effect of store atmosphere, brand identity, and social media marketing on purchasing decisions with purchase intention as a mediating variable. The sample of this research is the general public who have purchased coffee at the Janji Jiwa coffee shop. The sampling method used purposive sampling with a sample size of 110 respondents. The analysis tool used is multiple linear regression with the help of the SPSS version 25.0 program. The results of this study indicate that store atmosphere has no effect on purchase intention and purchase decision, brand identity has a positive effect on purchase intention and on purchase decisions, social media marketing has a positive effect on purchase intention and purchase decision, purchase interest has an effect on purchase decision, purchase interest does not mediate the effect of store atmosphere on purchase decisions, purchase intention mediates the influence of brand identity on purchasing decisions, and purchase intention mediates the influence of social media marketing on purchasing decisions